Nanoindentation-based micromechanical characterisation of ultra-high-performance concrete exposed to freezing–thawing. Issue 4 (23rd February 2022) - Xie, Ruifeng; Lu, Linjun; Qiao, Pizhong; Zhou, Zhidong
Abstract : The durability of ultra-high-performance concrete (UHPC) exposed to freezing–thawing (F–T) is closely associated with its micromechanical properties. In this study, the nanoindentation technique is employed to characterise the micromechanical properties of UHPC at different F–T cycles. It is observed that the indentation moduli of low-density calcium silicate hydrate, high-density calcium silicate hydrate, and calcium hydroxide in the studied UHPC decrease moderately with the decreasing ranges of 11.58, 14.56 and 3.3%, respectively, after undergoing 1500 F–T cycles. More micropores gradually form, converge and connect, and the volume fraction of micropores increases up to about 120%. The interfacial transition zone (ITZ) between steel fibre and cement paste is more prone to act as the weakest zone than that between fine sand and cement paste. The thickness of ITZ enlarges from 22 μm of the unconditioned stage to 60 μm at 1500 F–T cycles. Based on the micromechanical properties obtained from the nanoindentation test, the modulus of elasticity values of UHPC under different F–T cycles are predicted using the multiscale homogenisation model. It is proved that the combined micromechanical characterisation and multiscale homogenisation technique is capable of predicting the macromechanical properties of UHPC and their changes under F–T action.